Diseño de control de nivel y caudal del proceso de descargue de Biodiesel en ECOPETROL estación pozos colorados Santa Marta (2021)
The receipt system for filling Biodiesel at the Ecopetrol colorado well plant is carried out manually by an operator who has to connect the supply hose to the tank truck that supplies the system, which in turn has to manipulate the liquid flow. to the pumps through a pipeline directed with mechanical ball valves, the monitoring of the same system is done manually, waiting for the tank to fill and for the tank car to empty, causing excessive wear due to a Only the operator must be aware of the entire process of the tank truck, in addition to compromising the operator's health, due to the process gases and the exposure of the skin with biodiesel. This project tries to carry out the design of an electro-mechanical system that solves the problem of variable surveillance, carrying out the design and simulation in Simulink Matlab, establishing a PID control of the motor through a frequency variator, and simulating the system in the Logosoft programming software so that a feasibility study can be implemented and thus avoid contact with biodiesel as much as possible, in addition to optimizing the filling in the electrical way, improving the worker's working conditions and allowing an operator manipulate more than one filling island using the LOGO! Siemens.